Optical Characterization of Monodispersed Aqueous Cu2+-Doped CdS Nanoparticles Prepared Under Microwave Irradiation Conditions - Zhu, Wei; Shen, Qihui; Bao, Xinjian; Bai, Xiao; Li, Tingting; Zou, Mingqiang; Li, Jinfeng; Liu, Yan; Liu, Xiaoyang (Current Microwave Chemistry, 2015)
Aqueous CdS:Cu nanocrystals (NCs) have been successfully prepared under microwave irradiation conditions. It appears that these nanocrystals contain abundant copper ions in their central interior, and they can diffuse through the interface of CuS nucleus and CdS coated layers via cation exchange processes. The crystal structure, shapes and optical properties of nanocrystals were determined by X-ray diffraction, high-resolution transmission electron microscopy, UVVis absorption and photoluminescence spectroscopy analyses. The crystal structure of CdS:Cu nanocrystals appears to be zinc blende. Compared with pure CdS nanocrystals, the aqueous CdS:Cu nanocrystals possess an enlarged optical window ranging from 538 to 640 nm. Plus, they are highly emissive and exhibit excellent chemical/photochemical stability, as demonstrated by the fact that samples can be stored for months without visualizing precipitation or other changes.
Keywords: microwave